媒体在政治参与扮演的角色 ：以台湾与新加坡为例 = A study of the media's role in political participation in Singapore and Taiwan - 蒋晓亭 Chiong, Xiao Ting (2009)
本文研究台湾和新加坡媒体在这两个社会的政治参与中扮演的角色。笔者首先提出政治参与的定义，及政治参与在社会的重要性，接着厘清大众传媒和政治参与的关系，并且提出大众传媒在一个社会的政治参与扮演什么样的角色，及其重要性是什么。作者藉此理论探讨台湾政治参与从 80 年代开始的的改变，以及媒体在这段时期所经历的改革，并且对社会的政治参与的积极影响。接著以台湾为借鉴, 笔者考察新加坡政治参与的情况和新加坡媒体和政治参与的关系。笔者认为新加坡媒体应该向台湾媒体学习，制造一个环境和平台，让人民不会对对政治参与感到陌生，以加強国家的凝聚力，并且发展出公民社会。 This thesis is a study of how the media in Singapore and Taiwan plays a part in the political participation of the society. The writer first defines political participation and expounds on its importance in the society. Following which, the writer seeks to establish the relationship between the media and political participation, and studies the role that the media has in political participation and its importance in this. With this theory, this study continues to explore the political participation in Taiwan from the 80s, as well as the changes the media has faced in this period, and how these changes have brought about positive changes in the political participation in the society. By using Taiwan as an example, the writer continues to do a study on political participation in Singapore and the relationship that the local media has with political participation. The writer concludes that the media in Singapore should learn from the media in Taiwan, in this area of creating an environment and platform for political participation, so that the people would get more involved in the political affairs of the nation. In this way, we can increase the social cohesiveness in Singapore and develop a civil society.